The high-throughput solid-phase extraction of cis-cyclo(L-Leu-L-Pro) and cis-cyclo(L-Phe-L-Pro) from Lactobacillus plantarum demonstrates efficacy against multidrug-resistant bacteria and influenza A (H3N2) virus - Son, Jaeyoung; Hong, Yeonju; Seong, Hyeri; Oh, Yoon Sin; Kwak, Min-Kyu (Frontiers in Molecular Biosciences, 2024)
2,5-diketopiperazines are the simplest forms of cyclic dipeptides (CDPs) and have diverse frameworks with chiral side chains that are useful for drug development. Previous research has investigated the antimicrobial properties of proline-linked CDPs and their combinations in the culture filtrate (CF) of Lactobacillus plantarum LBP-K10 using anion exchange chromatography (AEC). However, the quantity of CDPs showcasing notable anti-influenza virus activity derived from AECs was generally lower than those originating from Lactobacillus CF. To address this issue, the study aims to propose a more efficient method for isolating CDPs and to introduce the antiviral combinations of CDPs obtained using a new method. The study employed a novel technique entailing high-throughput C18-based solidphase extraction with a methanol gradient (MeSPE). The MeSPE method involved increasing the methanol concentration from 5% to 50% in 5% increments. The methanol SPE fractions (MeSPEfs) eluted with methanol concentrations between 35% and 45% evinced substantial efficacy in inhibiting the influenza A/H3N2 virus via plaque-forming assay. MeSPEf-45, the 45% MeSPEf, exhibited exceptional efficacy in preventing viral infections in Madin-Darby kidney cells, surpassing both individual CDPs and the entire set of MeSPEfs. To identify the specific antiviral components of MeSPEf-45, all MeSPEfs were further fractionated through preparative high-performance liquid chromatography (prep-HPLC). MeSPEf-45 fractions S8 and S11 presented the highest activity against multidrug-resistant bacteria and influenza A/H3N2 virus among all MeSPEfs, with 11 common fractions. Antiviral fractions S8 and S11 were identified as proline-based CDPs, specifically cis-cyclo(L-Leu-L-Pro) and cis-cyclo(L-Phe-L-Pro), using gas chromatography-mass spectrometry. The combination of MeSPEf-45 fractions S8 and S11 displayed superior antibacterial and anti-influenza virus effects compared to the individual fractions S8 and S11. High-throughput MeSPE-derived MeSPEfs and subsequent HPLC-fractionated fractions presents an innovative approach to selectively purify large amounts of potent antimicrobial CDPs from bacterial CF. The findings also show the effectiveness of physiologically bioactive combinations that utilize fractions not containing CDP. This study provides the initial evidence demonstrating the antimicrobial properties of CDPs acquired through high-throughput SPE techniques.